Liberating Kosovo coercive diplomacy and U.S. intervention - Phillips, David L. (David Lawrence) 1959- (MIT Press, 2012)
A compelling account of the diplomatic and military actions that led to Kosovo's independence and their implications for future U.S. and UN interventions.